Effect of Inbound Tourism on The Rising of CO2 Emission (Evidence from 6 Top Destination SIDS Countries) - Mellani Indrie Pramudita; Dedy Yuliawan (Journal on Education, 2023)
The goal of this study is to examine the impact of the international tourist industry on Small Island Developing States (SIDS) nations, including the rise in gross domestic product (GDP) per capita due to international travel, which indirectly affects carbon dioxide emissions. In this work, panel data from 6 small island developing states between 2011 and 2019 were analyzed using the Two Stage Least Square (2SLS) analysis approach. Total CO2 Emissions (CO), Gross Domestic Product (GDPC) Growth, Tourist Arrivals (TOU), Population (POP), Energy Consumption (ENE), International Tourism Receipts (REC), and Unemployment Rate (UNE) are variables considered in this study. The study's findings show that while the variables Gross Domestic Product Per Capita Growth, Tourist Arrivals, Population, and Energy Consumption all have a positive impact on CO2 emissions, the variable Gross Domestic Product Per Capita Growth has a negative impact. Additionally, between 2011 and 2019 in 6 Small Island Developing States (SIDS) countries, CO2 emissions and international tourism receipts have a positive impact on GDP per capita growth whereas the unemployment rate has a negative impact.